IDENTIFICATION OF CARBOHYDRATES, PROTEINS, GLUCOSE, AND FATS IN FOOD INGREDIENTS AS A MEDIUM FOR BASIC SCIENCE LEARNING - Nabila Ananda; Abibah Hanum; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This practicum aims to identify and recognize the macronutrient content of carbohydrates, protein, glucose, and fat in various foods commonly consumed daily. This activity utilizes several simple tests using chemical reagents, such as Lugol's solution for carbohydrates, Benedict's solution for glucose, Biuret solution for protein, and oil paper for fat detection. Ten food items were tested, including bananas, bread, tempeh, tofu, eggs, fish, cheese, and green vegetables. Observations showed that each item has a different nutritional content. For example, carbohydrates are found in bananas and bread, protein in tempeh and eggs, glucose in bananas and bread, and fat in cheese and chicken. This practicum not only provides hands-on experience in conducting simple experiments but also serves as an effective learning tool for elementary school science. Through this activity, students can more easily understand the importance of nutritional content in food and practice observation skills and scientific thinking from an early age.